Aspartame precursor synthesis in water miscible cosolvent catalysed by thermolysin - Lee, Kong H.; Lee, Pat M.; Siaw, Y.S.; Morihara, Kazuyuki (Springer Science and Business Media LLC, 1992)
The synthesis of the dipeptide N-benzyloxycarbonyl-L- aspartyl-phenylalanine methyl ester, aspartame precursor, catalysed by thermolysin in aqueous and aqueous methanolic solutions was studied. Thermolysin with concentration as low as 10 μM in 25% methanol can catalyse the synthetic reaction. The optimum methanol compositions at 4°C and 37°C were 50% and 25% respectively where an increase in peptide yield of 85% was obtained for both conditions as compared to that in water.